Autologous keratinocyte suspensions accelerate epidermal wound healing in pigs - Svensjö, T; Yao, F; Pomahač, Bohdan; Eriksson, E (The Journal of surgical research, 2001)
BACKGROUND: Tissue culture techniques enable in vitro expansion of keratinocytes that can be used to treat burns and chronic wounds. These keratinocytes are commonly grafted onto the wounds as differentiated sheets of mature epithelium. Less is however known about the effects of transplanting the cells as suspensions. This study evaluated epidermal regeneration in fluid-treated skin wounds treated with suspensions of cultured and noncultured autologous keratinocytes. MATERIALS AND METHODS: Eighty-seven full-thickness excisional skin wounds were created on the back of 6 pigs and then transplanted with either cultured or noncultured autologous keratinocytes. The wounds were enclosed with liquid-tight chambers containing saline to provide a hydrated and standardized environment. RESULTS: Keratinocyte transplantation resulted in several cell colonies within the granulation tissue of the wound. These colonies progressively coalesced and contributed to a new epithelium. The origin of the transplanted keratinocytes was confirmed by histochemical staining of wounds transplanted with transfected keratinocytes expressing beta-galactosidase. Transplantation of 0.125 x 10(6), 0.5 x 10(6), and 2.0 x 10(6) cultured keratinocytes, and 0.5 x 10(6) and 5.0 x 10(6) noncultured keratinocytes, increased reepithelialization dose dependently over saline-treated controls. The epithelial barrier function recovered faster in transplanted wounds as demonstrated by less protein leakage over the wound surface on Days 7-10 as compared to control wounds. Wound reepithelialization and the number of keratinocyte colonies observed in granulation tissue were significantly less in wounds transplanted with noncultured keratinocytes compared to wounds seeded with cultured keratinocytes. CONCLUSION: Our study demonstrates successful transplantation of keratinocyte suspensions and their dose-dependent acceleration of wound repair. Selection of proliferative cells during culture and higher colony-forming efficiency may explain the greater effects observed with cultured keratinocytes.
Keywords: Wound Healing; Animals; keratinocyty; epidermis; Cells, Cultured; Female; autologní transplantace; zvířata; Epidermis; Transplantation, Autologous; Keratinocytes; prasata; Swine; ženské pohlaví; kultivované buňky; hojení ran